The Impact of Environmental and Sustainability in The Food and Beverage Company: A Case of Danone - Odebunmi Abayomi Tunde; Thiam Yong Kuek; Neha Rai; Pei Qian Loke; Er Xian Looi; M. Sanggita A/P Muguran; Mafe Olumwatunmise Irianuoluwayimika; Kriti Kumari; K. Sujan Kumar (AIBPM Publisher, 2026)
This study examines the sustainability practices implemented by Danone, a leading company in the food and beverage sector, and compares these efforts with industry benchmarks to assess their effectiveness. The research aims to determine how corporate sustainability strategies influence environmental performance and brand reputation. A quantitative design was used, with a survey questionnaire distributed through purposive sampling to gather customer perceptions of Danone’s sustainability initiatives. The collected data were analyzed using descriptive and inferential statistics to evaluate the relationship between sustainability practices and organizational outcomes. The findings indicate that Danone shows strong commitment to carbon neutrality, responsible sourcing, and circular packaging, although challenges persist in maintaining supply chain transparency and enhancing customer engagement. The study concludes that effective sustainability integration strengthens both environmental responsibility and corporate competitiveness. It recommends adopting transparent communication, continuous innovation, and stakeholder collaboration to support long-term sustainable growth.